ANALISIS KEBUTUHAN PERALATAN WORKSHOP KAYU BERDASARKAN JOBSHEET DI JURUSAN TEKNIK SIPIL FT-UNP - 576-583 , Zahratul Hasanah (Universitas Negeri Padang, 2015)
Abstract This research is qualitative descriptive research. The object of this research are primary manual equipment, supporting, portable and engineering equipment, of wood workshop in Civil Engineering Department, Faculty of Engineering of the State University of Padang. This research conduct to describe providing and needed equipment of wood workshop on the jobsheet. In this research researcher using the data formating equipment to identify providing and neededof equipment in wood workshop, the procedure of data collecting and counting the number of primary uses equipment, support equipment and portable equipment and machine tools used in the practice based jobsheet lectures. The results of a need analysis equipment in the main manual equipment and ancillary equipment used in the implementation of practice based jobsheet lectures and for some strightly damage, such as planers, saws, and jackhammer and equipment else that needs to be increased. The portable equipment and machine equipment can be said to be sufficient for practiced, but need to increase in order to be able to run more average practices. Key Word: Analysis, Needed, Equipment